DYNAMICS OF CRYSTALLIZATION, IMMISCIBILITY, AND BOILING FRONTS AT THE UPPER CONTACTS OF FLAT INTRUSIVE BODIES - Cherepanov A.N.; Cherepanova V.K.; Sharapov V.N. (My University, 2004)
The development of instability and retrograde saturation of magma melts as a result of their cooling are accompanied by the following complex dynamics of phase front evolution near the upper contact of igneous bodies at different stages of solidification: (1) the full spectrum of melt and fluid inclusions, may be formed in igneous rock crystals at a relatively high initial velocity of the solidus front propagation; (2) the composition of inclusions may start to change due to the gravitational segregation of gas and ore liquid fractions after an appreciable retardation of solidification front propagation and decrease of the temperature gradient in the frontal zone [1]; and (3) the proportions of inclusions in igneous rock minerals strongly depend on the wettability of the growing crystal surface.